Students’ Values of Various Training Profiles in the Digitalization of Society Context: Results of an Empirical Study - P. P. Deryugin; O. S. Bannova (Дискурс, 2022)
Introduction. The upcoming digitalization has a peculiar effect on the purposefulness of students' behavior, ensuring the transition to a new stage in the development of a postindustrial society. Social norms, values, and value orientations are subject to change. All this is formed into a new group of student digital values, which are shaped differently among students of various professional training profiles. These new phenomena involve the search for new methodological and methodological approaches to conducting empirical sociological research, the search for relevant approaches to measuring the digital values of students of various training profiles, and identifying special characteristics and meaningful features of these values.Methodology and sources. The research methodology is mixed, and is based on provisions about values and their specific forms of manifestation, particularly digital values (M. Weber,  F. Znanetsky, T. Parsons, E. Durkheim, A. Toffler). The digital society is a new perspective, the nature of which is inconsistently consistent with some of the principles of the traditional approach to the study of values that have developed in theoretical concepts earlier. The concepts of modern authors were used, such as M. Tomasello, F. Warneken, R. Hogan,  B.W. Roberts, E.F. Zeer, R. Kadakal, and Nguyen Hoang Huu. Results and discussion.The methodological approaches to the study of the values of the digital society as an object of study are generalized, in particular, the relevance of the system approach. The differences between the study of traditional values and the values of the digital society are shown, as a result of the analysis of which the accumulation of human capital by students with special (digital) characteristics could be considered as a main value of the digital society. Under these conditions, students of the humanitarian direction (journalists, sociologists) more often define for themselves value-goals as the most important values, and programming students define value-means as such. Conclusion. The study used a systematic approach to building a methodology for diagnosing digital values, which allows identifying the main value preferences of students of various training profiles. It is concluded that students of different training profiles understand the digital society differently, which implies different methodological approaches to the study and diagnosis of these values.